GAMBARAN TINGKAT STRESS PADA PASIEN COVID-19 DI RUANG ISOLASI AL-AQSA LT.6 RSU HAJI SURABAYA - Wibowo, Nugroho Ari; Setyiawan, Bayu; Agustin, Ratna; Ananditha, Aries Chandra; Rofiqi, Erfan (Indonesian Academia Health Sciences Journal, 2023)
Anxiety is a normal reaction to threatening and unexpected situations such as the Covid-19 pandemic. Possible stress-related reactions in response to the Covid-19 pandemic can include changes in concentration, irritability, anxiety, insomnia, reduced productivity, and interpersonal conflict, but are particularly true for directly affected groups (e.g. patients admitted to hospital isolation). The aim thid research to identify  the level of stress experienced by covid-19 patients in the Al-Aqsa isolation room . This article  This study used a descriptive method that was carried out on patients who were confirmed positive COVID-19 in the Al-Aqsa isolation room on the 6th floor of the Haji General Hospital Surabaya with the Accidental Sampling . The samples obtained were 30 respondents. The research instrument used in this research aiming at describing the stress experienced by respondents was DASS 42 questionnaireThe results showed that 23.3% of respondents experienced normal stress conditions, 53.3% experienced mild stress, 20.0% of respondents experienced moderate stress, and 3.3% of respondents experienced severe stress 7 (23.3%) respondents experienced moderate stress, 16 (53.3%) respondents experienced mild stress, 6 (20.0%) respondents experienced moderate stress, and 1 (3.3%) respondent experienced severe stress. Which is suspected to be influenced by age and gender factors